State of the art in subtotal cholecystectomy: An overview - Ramírez-Giraldo, Camilo; Torres-Cuellar, Andrés; Van-Londoño, Isabella (Frontiers in Surgery, 2023)
Introduction: Subtotal cholecystectomy is a type of surgical bail-out procedure indicated when facing difficult laparoscopic cholecystectomy due to not reaching the critical view of safety, inadequate identification of the anatomical structures involved and/or risk of injury. Materials and methods: A comprehensive search on PubMed were performed using the following Mesh terms: Subtotal cholecystectomy and Partial cholecystectomy. The PubMed databases were used to search for English-language reports related to Subtotal cholecystectomy between January 1, 1987, the date of the first published laparoscopic cholecystectomy, through January 2023. 41 studies were included. Results: Subtotal cholecystectomy’s incidence oscillates between 4.00% to 9.38%. Strasberg, et al., divided subtotal cholecystectomies in “fenestrating” and “reconstituting” types based on if the remaining portion of the gallbladder was left open or closed. Subtotal cholecystectomy can sometimes be a challenging procedure and is associated to a high rate of complications such as biliary fistula, retained gallstones, subhepatic or subphrenic collections, among others. Conslusions: Subtotal cholecystectomy is a safe alternative when facing difficult cholecystectomy in which the critical view of safety is not reached in order to avoid complications. A classification system should be implemented in surgical descriptions to compare the different surgical techniques employed. In order to avoid bile leakage and cholecystitis of the remnant gallbladder, the surgical technique must be performed skillfully. There is still a current lack of information on alternative techniques such as omental plugging or falciform patch in order to judge their utility. There needs to be further research on long-term complications such as malignancy of the remnant gallbladder.